Economic and Legal on The Deploying of Medical and Healthcare Robotics: Case Study on a Comparison of the European Union (EU), South Africa, and Thailand - Pichetworakoon, Arachamon; Kooptarnond, Nitchanand; Ngamchuensuwan, Sutthichai (CRRU Law, Political Science and Social Science Journal, 2021)
Europe is well placed to benefit from the potential of Artificial Intelligence (AI). It produces industrial and professional service robots for healthcare and plays an important role in developing and using software applications for companies. Surprisingly, the African Region and Thailand, neither of which is traditionally associated with robotics technology, are making good progress in the use and development of robots in the field of medical service and healthcare by promoting investment in robotics innovation. However, there are still several unclear aspects to be addressed by policymakers in these two regions. Although medical robots have shown great potential in these two areas by contributing to various healing processes, many limitations to the application of the technology as such have emerged in terms of economic policy, legal frameworks, the risk to privacy, and moral responsibility. Apparently, the main barrier holding back these two communities from being the next generation of automotive developers in medical robots is that legislative and investment policies governing robot activities are produced and enforced by different organizations separately. This effectively discourages not only management policy but also related action to support robotics innovation. Even though experts are creating increasingly advanced robot technology, regulation of its development is still lagging behind. This article will inform the social sciences, ethics, law, and market policy to find a solution where robots and humans can work side by side, with an emphasize on the application of legal and economic regulations relating to this growth in automation to encourage the status of the robots, bringing them to the forefront of the socio-scientific platform by applying documentary and action research methodology. In order to achieve this goal, economic policymakers and legal regulators have to engage in these agendas together with producers to establish how law and market policy should react to medical robots appropriately.